Peningkatan Keaktifan Lisan Siswa Melalui Video Animasi Pada Pembelajaran Seni Budaya Kelas VI Madrasah Ibtidaiyah Swasta Nurul Huda Muaro Jambi - Adang Ridwan; Ria Karmila (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study is about Increasing Students' Oral Activity Through Animated Videos in Arts and Culture Learning for Class VI of Nurul Huda Muaro Jambi Private Elementary School. This type of research is Classroom Action Research. The subjects in this study were class VI students. Data collection techniques used observation, interviews, and documentation. Data analysis techniques were carried out descriptively, quantitatively, and qualitatively. Based on the results of the study conducted in class VI of Nurul Huda Muaro Jambi Private Elementary School and through the indicators that have been determined, it can be seen that there is a difference in student learning activity after the application of animated video media in class VI. The success in increasing student learning activity in cycle I was recorded at 62.42, while in cycle II it increased to 88.03. This increase reflects a change in student behavior and involvement in learning, both from physical and mental aspects, as a result of a more interactive learning process.